The Diversification of Sources of Marketing Information by Business Activity Type – Research Results - Rawski, Marek (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The aim of the publication is to show the importance of different sources of marketing information in companies conducting different types business (manufacturing, services, trade) on the Polish market. The theses are formulated based on the results of research conducted by the Marketing Department of the Cracow University of Economics in 2013. The subject of the research was: “The scope and conditions of marketing used by companies in Poland”. For all the companies researched, the validity of the various sources of information is the same. The companies’ own experience and intuition prevail as the most important sources of information while the least important was research commissioned to specialised agencies. For the companies across all activity types, the importance of the various sources of information is the same. Manufacturing companies often use ready-made information from various external sources. Service companies prefer to use their own marketing research, market research outsourced to specialised agencies, and they also often use their own experience and intuition. Trading companies often use their own data.